2003
DOI: 10.1111/j.1572-0241.2003.07683.x
|View full text |Cite
|
Sign up to set email alerts
|

The Seroprevalence of Helicobacter Pylori in A Referral Population of Children in The United States

Abstract: The H. pylori seropositivity rate of GI referral children with symptoms of abdominal pain was significantly higher. H. pylori infection in early childhood was found to be associated primarily with the child's household size and socioeconomic status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
23
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 24 publications
11
23
0
Order By: Relevance
“…However, in this study, we found that the prevalence of H. pylori infection among children with RAP was three-and-a-half times greater than those without RAP. Similar findings have been reported in Saudi Arabia [37] and the United States [38]. In sub-Saharan Africa, RAP is common in children and helminthiasis is the proven etiology, particularly in low socio-economic settings [39].…”
Section: Discussionsupporting
confidence: 74%
“…However, in this study, we found that the prevalence of H. pylori infection among children with RAP was three-and-a-half times greater than those without RAP. Similar findings have been reported in Saudi Arabia [37] and the United States [38]. In sub-Saharan Africa, RAP is common in children and helminthiasis is the proven etiology, particularly in low socio-economic settings [39].…”
Section: Discussionsupporting
confidence: 74%
“…11,[26][27][28] However, the association of recurrent abdominal pain (RAP) and H. pylori is still debatable and other studies have reported an association between the two. 29,30 On the other hand, there is evidence against this association. First, if this association were true then H. pylori should have been seen more frequently in RAP cases than in controls.…”
Section: It Is Not Yet Clear Whether the Difference In Anthropometry mentioning
confidence: 90%
“…5 years) [2] . However, this prevalence is quite elevated (ranging from 22 to 45%) also in developed countries, when a population of symptomatic children is considered [3,4] .…”
Section: Introductionmentioning
confidence: 99%